The quantitative analysis of the bacteria found in the air of the dairy barn, and in the milk under varying conditions - Swift, Charles Bartholow; Logan, Ed A. (My University, 1905)
Introduction: In the consumption of milk the consumer puts up with the most varied conditions as regards the sanitary surroundings in the handling of milk. As the dairies in this country are under no immediate laws or rules, the cleanliness of the general dairy depends upon the owner. In some places where the dairies are subject to the city milk inspection laws of course all of them must be kept up to a certain standard of cleanliness and hygienic surroundings, but even then we find that the number of organisms that the milk contains, collected under these ordinary conditions, is exceedingly large and gives room for vast sanitary improvement. It is stated by some authorities that milk containing over 50,000 bacteria per cubic centimeter, (16 drops), is unfit for human use. However, examinations of milk from the various cities have shown a variation of from a few thousand to as many as fifty to eighty millions of germs per cubic centimeter. This, in itself, should demonstrate the necessity of a more careful handling of the milk. If these organisms were pathogenic (disease producing) one drop of such milk would be sufficient to exterminate a whole family. This shows that milk is a most favorable media for the growth of bacteria and it is very essential that the most sanitary conditions should prevail in the collecting and handling of this product. For even though milk may contain a small number of organisms at the time it is drawn, by the time it reaches the consumer the number may be increased a hundred, and sometimes a thousand times per cubic centimeter. The following experiments were conducted with the view of determining how the number of organisms which may gain access to the milk under varied conditions at the time it is drawn, can be reduced.
Citation: Swift, Charles Bartholow and Logan, Ed A. The quantitative analysis of the bacteria found in the air of the dairy barn, and in the milk under varying conditions. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Experiments Exposing Plates of Agar; In Windy conditions; In No Wind Conditions; Theses